Combining morphological and mitochondrial DNA data to describe a new species of Austroniscus Vanhöffen, 1914 (Isopoda, Janiroidea, Nannoniscidae) linking abyssal and hadal depths of the Puerto Rico Trench - Kaiser, Stefanie; Stransky, Bente; Jennings, Robert M.; Kihara, Terue Cristina; Brix, Saskia (Zootaxa, 2023)
Hadal trenches are perceived as a unique deep-sea ecosystem with fundamentally different communities compared to the nearby abyss. So far, however, scarce information exists about how populations are genetically linked within a trench and about mechanisms for species divergence. The present study presents the morphological and molecular-genetic characterization and description of a new nannoniscid species within the genus Austroniscus Vanhöffen, 1914 obtained from abyssal and hadal depths of the Puerto Rico Trench, NW Atlantic. Samples were collected as part of the Vema-TRANSIT expedition onboard RV Sonne in January 2015. Because of the large depth differences between sampling locations (4,552–8,338 m), we expected to find different species within the genus inhabiting abyssal and hadal sites. Initial morphological examination using traditional light microscopy and Confocal Laser Scanning Microscopy was paired with subsequent molecular analysis based on mtDNA (COI and 16S). Contrary to our assumptions, combined morphological and molecular species delimitation analyses (sGMYC, mPTP, ABGD) revealed the presence of only one species spanning the abyssal and hadal seafloor of the Puerto Rico Trench. In addition, comparison with type material could show that this species belongs to a new species, Austroniscus brandtae n. sp., which is described herein. Incongruence between some species delimitation methods suggesting the presence of multiple species is interpreted as strong genetic population structuring within the trench, which is also supported by the analysis of the haplotype networks. The geographic and bathymetric distribution of Austroniscus species is discussed. The species described herein represents the first in the genus Austroniscus from the Atlantic Ocean and the deepest record of the genus to date, and hence significantly expanding previously known limits of its geographic and bathymetric range.